Islamic Environmental Conservation: Navigating the Challenges and Demands of Globalization - Thohir, Umar Faruq; Gunaryo, Achmad; Suwandaru, Agung; Raharjo, Raharjo (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
Addressing the issue of natural destruction from a religious perspective requires an additional dimension that focuses on solutions to the underlying causes of environmental degradation. Scholars contend that the degradation of nature stems from a spiritual crisis afflicting humanity. To address this challenge, this study employs a qualitative method with content analysis as its analytical tool to uncover a value system capable of revitalizing human spirituality within an ecocentric framework. The research reveals that eco-theology, eco-fiqh (fiqh al-bī’ah), and eco-sufism all share a common theme in exploring divine entities through the natural world. The equilibrium of nature emerges as the central element that enhances worship, servitude, and the embodiment of divine values, thereby enriching human spirituality. Consequently, the cultivation of human spirituality is achieved through the processes of utilization (al-intifā’), the abstraction of divine values (al-i'tibār), and conservation (al-iṣlāḥ). These three environmental ethics examine human behavior towards the universe and delve into the relationships among all living beings within this vast universe.